Spatial and temporal analysis of marine water pollution in Port Klang: developing a GIS database for assessing patterns and trends - Kamar Supardi, Izyan Hakimah; Mohamad Abdullah, Nazirah; Tugi, Astina; Ismail, Badrul Hisham (2024)
This study focuses on the assessment of marine water quality in Port Klang, with a particular emphasis on the spatial and temporal analysis of water quality parameters. The research investigates the sources of water pollution in the area, including industrial waste, nonpoint sources, heavy metals, and land use. The study utilizes geographic information systems (GIS) and the Inverse Distance Weighted (IDW) interpolation technique to map marine water quality parameters and analyze their spatial distribution. Additionally, a temporal analysis is conducted to identify trends, seasonal variations, and irregularities in water quality over an eight-month period. The study reveals TSS and O&G exceeding the allowable limits in certain locations. However, the analysis demonstrates a decreasing trend in TSS and O&G concentrations over time, indicating positive developments in water quality. The findings underscore the importance of continued monitoring and the implementation of pollution control measures to ensure sustainable and healthy marine water ecosystems in Port Klang